Developing Instructional Material And Strategies For Buginese Learners In The Crash Course Program at Neroa School - Ahyadi, Ahyadi; Jabu, Baso; Nur, Rafi'ah (La Parole : Journal of Language Teaching and Pedagogy, 2021)
This research is a development research that aims to develop an instructional strategy and suitable materials for an English crash course program at Neroa School, a non-formal educational institution in Soppeng Regency, South Sulawesi, Indonesia. This research is a continuation of previous research conducted by researchers that focused on identifying the needs of Buginese learners in learning English as a foreign language. Researchers adopted the ADDIE Model developed by Branch (2009), covering the stages of analysis, design, develop, implementation, and evaluation. The research instrument used was a questionnaire at the stage of needs analysis and product validation as well as pre-test and post-test sheets at the implementation stage before the evaluation process which contained product revisions. Data analysis is presented in a statistically qualitative descriptive form. This research produces a teaching material with the genre of Grammar for Speaking accompanied by teaching strategies that are in line with the material.